Variasi fenotip cadel (disartria) pada populasi mahasiswa Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Padang - Ahmad Hambali; Alifah Hazelia Elviana; Afifatul Achyar (Genetikawan Muda Indonesia, 2025)
Lisp (Dysarthria) is an abnormality in the nervous system that can affect the performance of the articulatory muscles or speech organs. The Hardy-Weinberg Law states that the frequency of genes in a population remains constant from one generation to the next if there are no evolutionary processes such as migration, mutation, natural selection and gene flow. This research aims to analyze the variation in the Lisp (Dysarthria) phenotype in the Biology Faculty student population. Mathematics and Natural Sciences, Padang State University. Data was obtained through an online questionnaire that identified the predominance of Lisp (Dysarthria) (Dysarthria or not Dysarthria). The results of the study showed that Lisp (Dysarthria) was found in a number of students in a proportion 10 people out of a total of 105 respondents. Analysis using the Hardy-Weinberg law shows that the frequency of dominant (p) and recessive (q) alleles. The frequency of the recessive allele (q) which causes the absence of lisp (dysarthria) is around 0.30, while the frequency of the dominant allele (P) is around 0 .7. Based on calculations, the estimated genotype proportions are 49% homozygous dominant (CC), 42% heterozygous (Cc), and 9.6% homozygous recessive (cc). These results indicate that the population of FMIPA UNP biology students is in Hardy-Weinberg equilibrium regarding the characteristic of lisp (dysarthria). Phenotypic variations of Lisp (Dysarthria) provide an overview of genetic diversity in the population environment of Biology students, Faculty of Mathematics and Natural Sciences, Padang State University and can be the basis for further research regarding the relationship between genetic factors and phenotypic expression in human populations. Keywords: Disartria, Phenotype, Variation, Student, Genetics. ABSTRAK Cadel (Disartria) merupakan kondisi kelainan pada sistem saraf yang dapat memengaruhi kinerja otot artikulator atau organ bicara. Hukum Hardy-Weinberg menyatakan frekuensi gen dalam suatu populasi tetap konstan dari satu generasi ke generasi berikutnya jika tidak ada proses evolusi seperti migrasi, mutasi, seleksi alam dan aliran gen.Penelitian ini bertujuan untuk menganalisis variasi fenotip Cadel (Disartria) pada populasi mahasiswa Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Padang.Data diperoleh melalui kuisioner daring yang mengidentifikasi dominasi Cadel(Disartria) (Disartria atau tidak Disartria).Hasil penelitian menunjukkan bahwa Cadel (Disartria) ditemukan pada sejumlah mahasiswa dengan proporsi 10 orang dari jumlah total responden 105 orang. Analisis menggunakan hukum Hardy-Weinberg menunjukkan bahwa Frekuensi alel dominan (p) dan resesif (q).frekuensi alel resesif (q) yang menyebabkan tidak adanya Cadel (Disartria) adalah sekitar 0,30, sedangkan frekuensi alel dominan (P) adalah sekitar 0,7. Berdasarkan perhitungan, proporsi genotip yang diestimasi adalah 49% homozigot dominan (CC), 42% heterozigot (Cc), dan 9,6% homozigot resesif (cc). Hasil ini mengindikasikan bahwa populasi mahasiswa biologi FMIPA UNP berada dalam keseimbangan Hardy-Weinberg terkait sifat Cadel (Disartria) . Variasi fenotip Cadel (Disartria) memberikan gambaran keberagaman genetik di lingkungan populasi mahasiswa Biologi Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Padang dan dapat menjadi dasar untuk penelitian lebih lanjut mengenai hubungan antara faktor genetik dan ekspresi fenotipik pada populasi manusia. Kata kunci: Disartria, Fenotip, Variasi, Mahasiswa, Genetika.